Tailoring Physicochemical and Technological Properties of α-Glucans Through Mutations of GTFA from Lactobacillus Reuteri E81 - Gokcan, Hande; Ispirli, Humeyra; Dertli, Enes (SPRINGER, 2026)
Glucansucrases catalyze the production of alpha-glucans using sucrose as substrate with distinct physicochemical characteristics originates from mainly the type of linkages, degree of branching and molecular mass. New forms of alpha-glucans can be produced by applying specific mutations to glucansucrases. In this study, a single and double mutation at Leu933 and Leu935 sites of glucansucrase E81 was applied and L933I and L933I-L935F sites modified glucansucrase was obtained. Structural characterisation of bioengineered alpha-glucans revealed that ratio of (1 -> 3):(1 -> 6) linked alpha-Glc units altered at L933I whereas no (1 -> 3)-linked alpha-Glc units were presented for L933I-L935F modified glucansucrase detected by NMR analysis. Both bioengineered alpha-glucans had lower molecular weights in comparison to glucan E81 detected by GPC analysis. TGA and DSC analysis were applied to detect the thermal profiles of bioengineered alpha-glucans whereas FTIR and XRD analysis were applied to determine the alterations in the structural and physical nature of the bioengineered alpha-glucans, respectively. Finally, SEM and AFM analysis were applied to explore the morphological modifications of the bioengineered alpha-glucans. This study provides a better understanding for the potential role of final glucan structures on their physicochemical characteristics. Keywords: glucansucrase; carbohydrate engineering; mutation.
Keywords: Glucansucrase; Carbohydrate engineering; Mutation; SITE-DIRECTED MUTAGENESIS; STRUCTURAL-ANALYSIS; FUNCTIONAL ROLES; EXOPOLYSACCHARIDE; DEXTRAN; GTF180; SPECIFICITY; ENZYMES; REUTERANSUCRASE; TRANSFORMATION; Food Science & Technology